1996
DOI: 10.1111/j.1349-7006.1996.tb03149.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent Induction of 8‐Hydroxyguanine and Preneoplastic Foci in Rat Liver by a Food‐derived Carcinogen, 2‐Amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline, at Low Dose Levels

Abstract: Male F344 rats were administered 2‐amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline (MeIQx) in the diet at doses of 200, 50, 12.5, 3.2, 0.8, 0.2 and 0.05 ppm for 6 weeks, and partially hepatectomized 1 week after the beginning of MeIQx administration. Quantitative values for glutathione S‐transferase placental form (GST‐P)‐positiye foci in the liver were dose‐dependently increased by the MeIQx treatment. 8‐Hydroxyguanine (8‐OHG) levels assessed after 1 week of dietary MeIQx administration were also dose‐dependently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 41 publications
1
16
1
Order By: Relevance
“…56 The fact that the level of 8-OHdG formation showed a statistical significant decrease at a dose of 0.005 ppm DDT compared to the concurrent control group in our study, thus provides further evidence in favour of a role for change in CYP3A2 protein expression. Although we also examined OGG1 mRNA expression, this proved to be unchanged.…”
Section: Discussionsupporting
confidence: 62%
“…56 The fact that the level of 8-OHdG formation showed a statistical significant decrease at a dose of 0.005 ppm DDT compared to the concurrent control group in our study, thus provides further evidence in favour of a role for change in CYP3A2 protein expression. Although we also examined OGG1 mRNA expression, this proved to be unchanged.…”
Section: Discussionsupporting
confidence: 62%
“…G3 T transversions are the most commonly observed mutations, but other point mutations have been documented. Increases in 8-OH-Gua levels have also been correlated with carcinogenesis in numerous studies [Nakae et al, 1997;Yamaguchi et al, 1996;Asami et al, 1996;Kato et al, 1996;Floyd, 1990]. Therefore, the 3(Ϯ1)-fold dose-dependent increase of 8-OH-Gua levels observed in type II cells exposed to H 2 O 2 suggests that they have been predisposed to mutagenesis.…”
Section: Discussionmentioning
confidence: 81%
“…However, clear dose-dependence was not observed, and reversible alteration of liver DNA after administration of genotoxic carcinogens has been demonstrated. 19,32,33) In one study, 8-OHdG levels assessed after 1 week of dietary MeIQx administration were dose-dependently increased, but this was not the case at the end of the treatment period, especially with the higher-dose groups.…”
Section: Meiqx Treatmentmentioning
confidence: 99%
“…8,10,35) Recently, quantitative data for GST-P-positive foci comprising very small numbers of hepatocytes have been used for detection of liver carcinogens and assessment of hepatocarcinogenic risk. 11,17,32,36) It has been demonstrated that levels of MeIQx-DNA adducts linearly increase from very low doses, but this is not the case for GST-P-positive foci development. 11,17) Our present data also demonstrated that maternal exposure to MeIQx during the period of pregnancy and lactation did not increase the number of GST-P-positive foci in the liver despite causing genetic damage.…”
Section: Meiqx Treatmentmentioning
confidence: 99%